Monitoring the state of public health in the conditions of a full-scale war in Ukraine - O.M. (Економіка, управління та адміністрування)
Health care is one of the most important economic resources of society. A change in a person’s health affects their quality of life, work productivity, the educational process, the mortality rate, and economic processes in general. The full-scale invasion of the russian federation into Ukraine caused irreversible and extremely negative consequences for the health of the population. Armed aggression has led to violence, trauma, injuries that can be serious and lead to death. Territories where active hostilities are taking place are too dangerous for health and life, as constant stress and excitement disturb the psychological state of citizens. During military conflicts, a number of problems arise, namely: a demographic crisis, access to medicine in occupied and liberated territories is disrupted, and the financial inability of the population increases. Health care of citizens in wartime is an important problem for the entire health care system. The problem of monitoring public health as an object of public administration in the health care system is an important and relevant issue under the conditions of exposure to risks that occur during war. The assessment of the state of morbidity of the population contributes to the effective adoption of relevant management decisions in the medical field regarding the prevention of diseases, strengthening and protection of health.